Exploring functional transitions of the 2’-dG riboswitch aptamer - Erdong Ding; Susmit Narayan Chaudhury; Karissa Y. Sanbonmatsu; José N. Onuchic (Proceedings of the National Academy of Sciences, 2026)
Riboswitches are structural elements in the 5’ untranslated region of mRNAs that adopt different conformations under different conditions. Transitions between these different states are involved in controlling gene expression and occur on relatively slow timescales. The RNA structure based model is a coarse-grained description developed by combining structural information with electrostatic interactions for RNA molecules. The simplicity of this model allows for the exploration of longer timescales and the entire energy landscape of the riboswitch aptamer which is not possible with physical force fields. Molecular dynamics simulations using this simpler representation are consistent with explicit solvent simulations and SHAPE and NMR experiments. Our simulations reveal a temperature range, which includes room temperature, where the P1 helix is stable in the presence of ligand binding while flexible in the ligand-free state. These simulations suggest a multibasin free energy profile for the aptamer domain of the 2’-dG riboswitch, where the secondary structures are stably formed with a different organization of the tertiary structures, especially in the absence of the ligand. It is also suggested that the Mg 2+ ions have a significant stabilizing effect, especially on the tertiary structures and on the regulatory helix P1, creating magnesium-mediated attractive interactions between phosphate groups in some cases. The mechanism proposed by experimentalists for the functional transition requires the breaking of the P1 helix. This process occurs on relatively slow timescales, and therefore necessitates the proposed model which allows direct connection to experimental observations.